The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1109/77.233350
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization of amorphous and nanocrystalline NdBa/sub 2/Cu/sub 3/O/sub 7-x/ and GdBa/sub 2/Cu/sub 3/O/sub 7-x/

Abstract: Using a novel melt-spinning technique, we have produced both amorphous and nanocrystalline NdBa~Cu307-~ and GdBa2C~307-~ materials. Samples melt-spun in 0 2 consist' of nanocrystals with the tetragonal 123 structure while those processed in N2 show an amorphous matrix with small amounts of crystalline BaCu202, as shown by XRD and TEM studies. The difference is due to the strong dependence of the phase relations on the 0 2 partial pressure. Superconductivity can be fully restored by heating above 1000°C followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Moreover, the amorphouslike phase was more reactive to the atmospheric gasses than the Nd123 phase, which is subject to decomposition. [9][10][11] As discussed in Sec. This is also associated with the fact that XRD results at room temperature did not indicate any distinct features of the amorphous phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the amorphouslike phase was more reactive to the atmospheric gasses than the Nd123 phase, which is subject to decomposition. [9][10][11] As discussed in Sec. This is also associated with the fact that XRD results at room temperature did not indicate any distinct features of the amorphous phase.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] It was suggested that the amorphous phase was obtained and the Nd123 phase crystallized from the amorphous phase around 630°C by high-temperature x-ray diffrac-tion (HTXRD) at heating condition of 6.5°C/min. [9][10][11] It was suggested that the amorphous phase was obtained and the Nd123 phase crystallized from the amorphous phase around 630°C by high-temperature x-ray diffrac-tion (HTXRD) at heating condition of 6.5°C/min.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] One particularly interesting finding is that the substitution of Nd and other RE elements for yttrium, either full or partial, has been found to have little or no deleterious effect on the electronic properties of the material. A great deal of work has been put into fully characterizing REsubstituted 1:2:3 in terms of the crystal structure and the phase transformations that occur.…”
Section: Introductionmentioning
confidence: 99%